Reason Taking the Reins From Impulsivity: The Promise of Dual-Systems Thinking for Criminology. (November 2015) - Mamayek, Chae; Loughran, Thomas; Paternoster, Ray
Aspects of criminological theory are premised on the belief that criminals make poor decisions. There have been suggestions that individual differences in self-control, willpower, impulsivity, time orientation, or more recently, thoughtfully reflective decision making (TRDM) influence choices and, ultimately, deviant outcomes. While much of the literature suggests there are differences among these concepts, they are often used interchangeably or at least noted to share common ground. Using survey data collected from university undergraduate students, this article explores the conceptual and empirical overlap and areas of distinction between key theoretical constructs. Using hypotheses derived from a dual-systems model, findings suggest impulsivity, self-control, temptation, and TRDM are distinct but interrelated constructs. Impulsivity was positively related to intentions to drink and drive in a hypothetical scenario, but temptation, self-control, and TRDM had no significant effect on intentions. Consistent with a dual-systems conceptualization, we found impulsivity and self-control work in tandem, as the risk of drinking and driving was highest for those respondents who were highly impulsive and had low self-control. Future research may seek to use a dual-system model to further reconcile trait-based and decision-based models of criminological theory.